Public Sector Audit: Implications on Accountability & Financial Performance of Parastatals in Zambia - Chrispin M. MWANGO; Chanda G.M. SHIKAPUTO (Communications of International Proceedings, 2022)
The public sector in Zambia is categorized in five main categories namely; the Central Government, Local Government, Parastatals and Statutory organizations. This study focused on the Parastatals also called State Owned Entities (SOEs). The SOEs have a mandate to promote diversification, industrialization and economic growth. However these SOEs have continued to score poor financial performance as usually reported by Auditor General in the public sector audit reports. If these SOEs continue to record poor financial and operational results then the aspect of industrialization, diversification and contribution to economic growth cannot be achieved.  The National Audit Office uses the Public Audit Act to audit the SOEs and reports to Parliament. The SOEs have been poorly performing financially and in accountability, hence this study to evaluate the implications of Public Sector Audit on SOEs’ Financial Performance and Accountability for a period of thirteen years. The research approach was a quantitative one with the aim to establish empirical statistical evidence to current theories that audit can improve organizational performance. This study embarked on establishing conclusive statistical evidence to the concerts and theories like (Shariman et. al, 2017) that audit can reduce inefficiencies and increase business performance. The aim was establish a relationship between public sector audit and internal organizational   inefficiencies that lead to accountability and better financial performance using secondary data   on the matters raised by the Office of the Auditor General on Parastatals in Zambia. The secondary data was collected for a period of thirteen (13) years for thirty seven (37) Parastatals in Zambia and analyzed using SPSS package. It was overserved that each time public sector audit was conducted using the combination of the three methods namely financial audit, performance audit and compliance audit the result on internal inefficiency improved by 0.699 time or 69.9%. It was concluded that public sector audit has implications of the internal organizational efficiency that lead to improvements in accountability and financial performance of Parastatal entities.
Keywords: Public Sector Audit; Accountability; Financial Performance & Parastatals